Variations of methane conversion process with the geometrical effect in rotating gliding arc reactor. (6th November 2020) - Kang, Hongjae; Choi, Seongil; Jung, Chan Mi; Kim, Kwan-Tae; Song, Young-Hoon; Lee, Dae Hoon
Abstract: Controllability of the kinetic path of methane conversion in plasma driven oxidation reaction is investigated. Different geometries in a rotating gliding arc reactor are adopted to control reaction paths in methane oxidation reaction. Diverging and converging type reactor product different reaction environments in view point of both the reaction time and the degree of thermal activation. In the diverging reactor, the partial oxidation process is dominant with high methane conversion because the diverging section facilitates to elongate the arc length and decrease the flow velocity. Thus, the convective and radiative heat transfer from the arc column to the reactants could be enhanced. The role of plasma in the diverging reactor is mainly igniting and sustaining the partial oxidation, which is rather different from that in the converging reactor where the plasma plays as a heat source for thermal pyrolysis of methane with the help of focusing thermal energy of the arc. Highlights: Geometry of rotating gliding arc reactor affects methane oxidation processes. Diverging type reactor head is beneficial for the partial oxidation process. Converging type reactor head is advantageous for the pyrolysis process.